2019
DOI: 10.1094/pdis-02-19-0322-re
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Phytopathological Reaction of Wild and Cultivated Olives as a Means of Finding Promising New Sources of Genetic Diversity for Resistance to Root-Knot Nematodes

Abstract: Olive (Olea europaea L.) is one of the most important fruit crops in the Mediterranean Basin, because it occupies significant acreage in these countries and often has important cultural heritage and landscape value. This crop can be infected by several Meloidogyne species (M. javanica, M. arenaria, and M. incognita, among others), and only a few cultivars with some level of resistance to these nematodes have been found. Innovations in intensive olive growing using high planting densities, irrigation, and subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Corroborating this hypothesis, the ‘Galega vulgar’ from WOGB in the work of Díez et al ( 2015 ), analyzing a data set of wild and cultivated olive trees with SSRs to estimate its most probable demographic model, belongs to a Central cluster that shows signs of a mixture between cultivated and wild olives. So, it is possible that ‘Galega vulgar’ still holds undomesticated forms, which might be beneficial for the selection of interesting phenotypes [such as resistant traits studied by Jiménez-Fernández et al ( 2016 ) and Palomares-Rius et al ( 2019 ) in wild olive trees] in breeding programs. As shown in Lazović et al ( 2018 ), several east Adriatic olive tree varieties revealed many differences in their intra-varietal diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating this hypothesis, the ‘Galega vulgar’ from WOGB in the work of Díez et al ( 2015 ), analyzing a data set of wild and cultivated olive trees with SSRs to estimate its most probable demographic model, belongs to a Central cluster that shows signs of a mixture between cultivated and wild olives. So, it is possible that ‘Galega vulgar’ still holds undomesticated forms, which might be beneficial for the selection of interesting phenotypes [such as resistant traits studied by Jiménez-Fernández et al ( 2016 ) and Palomares-Rius et al ( 2019 ) in wild olive trees] in breeding programs. As shown in Lazović et al ( 2018 ), several east Adriatic olive tree varieties revealed many differences in their intra-varietal diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Wild olive forests are native to Tunisia and wild/feral olive forms can be found in natural and agrarian ecosystems [65]. This germplasm appears promising for resistance to defoliating Verticillium [85] and root-knot nematodes [86], as well as drought tolerance [87]. In addition, it is considered a resource for improving olive oil's quality.…”
Section: Olive Breeding In Tunisiamentioning
confidence: 99%
“…The sections were obtained with a rotary microtome at 8 μm and immediately attached to adhesive-treated glass slides. After removal of paraffin, the sections were stained with a combination of tannic acid-ferric chloride, safranin, and fast green, by which nuclei, chromosomes, and lignified or suberized cell walls stain red, cytoplasm and cellulosic cell walls stain green, and the tannic acid-iron chloride aids in cell wall definition and is considered to be a general test for phenols (Jensen 1962;Reeve 1951;Ruzin 1999;Palomares-Rius et al 2019). The stained tissue was evaluated under a light microscope to observe the process of parasitic invasion into sunflower tissues.…”
Section: Histopathological Studymentioning
confidence: 99%